2016
DOI: 10.1007/s10763-016-9736-8
|View full text |Cite
|
Sign up to set email alerts
|

A Teaching-Learning Sequence of Colour Informed by History and Philosophy of Science

Abstract: In this work, we present a teaching-learning sequence on colour intended to a pre-service elementary teacher programme informed by History and Philosophy of Science. Working in a socio-constructivist framework, we made an excursion on the history of colour. Our excursion through history of colour, as well as the reported misconception on colour helps us to inform the constructions of the teaching-learning sequence. We apply a questionnaire both before and after each of the two cycles of action-research in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
(60 reference statements)
1
6
0
1
Order By: Relevance
“…Note that the colors presented in the figures of this work, as in the case of any graphic presentation in computer monitors, television, and video projectors, are formed by additive synthesis, even though they intend to represent subtractive synthesis. According to Mauri ́cio et al, 11 there is no need to consider the wavelike aspect of light in teaching−learning about the basic aspects of color.…”
Section: ■ Methodology Definitions and Considerations On Color Mixing...mentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the colors presented in the figures of this work, as in the case of any graphic presentation in computer monitors, television, and video projectors, are formed by additive synthesis, even though they intend to represent subtractive synthesis. According to Mauri ́cio et al, 11 there is no need to consider the wavelike aspect of light in teaching−learning about the basic aspects of color.…”
Section: ■ Methodology Definitions and Considerations On Color Mixing...mentioning
confidence: 99%
“…The differentiation between pigment-color and light-color stimulus 16 is particularly important, considering that their mixing models are different. Additionally, Mauri ́cio et al 11 reported general misconceptions on color learning from elementary students, indicating that the Aristotelian conception that colors are an inherent property of material prevails.…”
Section: ■ Class Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…also when coloured light illuminates a coloured object [4,7]; that natural light (such as sunlight) is not composed of a mixture of colours, but considered as 'pure' and colourless [8]. Sometimes, as is the case in other fields of physics, these conceptions emulate historical theories about colour, which predate the emergence of the scientific method [9]. Misconceptions about the mechanism of vision contribute to a poor understanding of colour; a widespread model among students is that of light as a facilitator of vision: ambient light reveals colours and allows them to be seen, but it has no other special relationship to vision or the eye [10].…”
Section: Previous Research On the Teaching-learning Of Colourmentioning
confidence: 99%
“…Dados os impactos da ciência e da tecnologia em nossa vida cotidiana, ao longo das últimas décadas o ensino de ciência tem enfatizado a importância da formação de cidadãos crítico-refl exivos para a vivência em sociedade, além da aprendizagem de conteúdos científi cos. Neste cenário, uma vertente em destaque, em especial na área das Ciências da Natureza, é o desenvolvimento e trabalho com sequências de ensino-aprendizagem (SEA) como forma de aproximar a ciência escolar com o cotidiano dos alunos, evidenciando que o conhecimento científi co contribui para interpretações do mundo material (VÁZQUEZ-ALONSO et al, 2016;GUISASOLA et al, 2017;KNEUBIL;MAURÍCIO et al, 2017;SAVINAINEN et al, 2017;;SILVA;COLOMBO JUNIOR, 2017).…”
Section: Considerações Iniciaisunclassified